Discursos da igualdade/omissão: análise de legislação sobre igualdade entre os sexos na educação - Luísa Saavedra (Universidade do Minho, 2001)
In this article, legal documents on equal oportunities between sexes are analysed. We consider only those documents which specifically concern primary and secondary education. First, these documents are analysed one by one. Then, a global critical approach is adopted.